In vivo detection of microstructural spinal cord lesions in dogs with degenerative myelopathy using diffusion tensor imaging. (22nd December 2020) - Johnson, Philippa J.; Miller, Andrew D.; Cheetham, Jonathan; Demeter, Elena A.; Luh, Wen‐Ming; Loftus, John P.; Stephan, Sarah L.; Dewey, Curtis W.; Barry, Erica F.
Abstract: Background: Degenerative myelopathy (DM) in dogs is a progressive neurodegenerative condition that causes white matter spinal cord lesions. These lesions are undetectable on standard magnetic resonance imaging (MRI), limiting diagnosis and monitoring of the disease. Spinal cord lesions cause disruption to the structural integrity of the axons causing water diffusion to become more random and less anisotropic. These changes are detectable by the technique of diffusion tensor imaging (DTI) which is highly sensitive to diffusion alterations secondary to white matter lesion development. Objective: Perform spinal DTI on cohorts of dogs with and without DM to identify if lesions caused by DM will cause a detectable alteration in spinal cord diffusivity that correlates with neurological status. Animals: Thirteen dogs with DM and 13 aged‐matched controls. Methods: All animals underwent MRI with DTI of the entire spine. Diffusivity parameters fractional anisotropy (FA) and mean diffusivity (MD) were measured at each vertebral level and statistically compared between groups. Results: Dogs with DM had significant decreases in FA within the regions of the spinal cord that had high expected lesion load. Decreases in FA were most significant in dogs with severe forms of the disease and correlated with neurological grade. Conclusions and Clinical Importance: Findings suggest that FA has the potential to be a biomarker for spinal cord lesion development in DM and could play an important role in improving diagnosis and monitoring of this condition.